Analysis of User Satisfaction Level of Information System Library Using PIECES Framework - Indrawati, Indrawati; Lokapitasari Belluano, Poetri Lestari; Harlinda, Harlinda; Tuasamu, Fatima A.R; Lantara, Dirgahayu (ILKOM Jurnal Ilmiah, 2019)
The use of information systems requires special management and management, so this system is commonly referred to as a management information system. In it there are various activities ranging from system planning, maintenance, to measuring performance. In running a library information system, software and hardware are needed as well as humans as operators. The above components must be activities that are interconnected so that the library can run smoothly. To determine whether the components of the information system are running well, it requires an evaluation process.The purpose of this study is to measure the level of satisfaction of system users and to determine the strengths and weaknesses of the system in the use of library information systems. The method used is the analytical method PIECES Framework, which consists of several points of analysis, namely: Performance, Information and Data, Economics, Control and Security, Efficiency, and Service. Where each analysis point is a reference for evaluation and analysis of information systems.The results of this study are web applications that are able to analyze the level of user satisfaction with the library information system using the PIECES Framework analysis method and equipped with a satisfaction level reporting chart of the system measured in the 2018 period